Genetic characterization of Pseudomonas fluorescens SBW25 rsp gene expression in the phytosphere and in vitro. - Jackson, R; Preston, G; Rainey, P (2005)
The plant-colonizing Pseudomonas fluorescens strain SBW25 harbors a gene cluster (rsp) whose products show similarity to type III protein secretion systems found in plant and animal pathogens. Here we report a detailed analysis of the expression and regulation of the P. fluorescens rsp pathway, both in the phytosphere and in vitro. A combination of chromosomally integrated transcriptional reporter fusions, overexpressed regulatory genes, and specific mutants reveal that promoters controlling expression of rsp are actively transcribed in the plant rhizosphere but not (with the exception of the rspC promoter) in the phyllosphere. In synthetic medium, regulatory (rspL and rspR) and structural (rspU, plus the putative effector ropE) genes are poorly expressed; the rspC promoter is subject to an additional level of regulatory control. Ectopic expression of regulatory genes in wild-type and mutant backgrounds showed that RspR controls transcription of the alternate sigma factor, rspL, and that RspL controls expression of gene clusters encoding structural genes. Mutation of rspV did not affect RspR-mediated expression of rspU. A search for additional regulators revealed two candidates--one with a role in the conversion of alanine to pyruvate--suggesting that expression of rsp is partly dependent upon the metabolic status of the cell. Mutations in rsp regulators resulted in a significant reduction in competitive colonization of the root tips of sugar beet seedlings but also caused a marked increase in the lag phase of laboratory-grown cultures, indicating that rsp regulatory genes play a more significant general role in the function of P. fluorescens SBW25 than previously appreciated.